Risk factors for cardiovascular disease among active adult US scuba divers - Buzzacott, Peter; Edelson, C.; Bennett, C.; Denoble, P. (Sage Publications, 2018)
Cardiovascular factors among uninjured active adult recreational scuba divers in the USA are described. Scuba diving as an activity was included in 2011, 2013, and 2015 Behavioral Risk Factor Surveillance System data. One-third of active US scuba divers were aged =50 years and/or reported prior high cholesterol, around half were overweight, more than half reported having smoked cigarettes, and 32% reported hypertension or borderline hypertension. High cholesterol, hypertension, high body mass index, and smoking status should all be addressed during routine diving fitness physician assessments, to reduce the risk of mortality while diving.